Interleukin -6 and C- reactive protein profiles in Hepatitis C virus patients - Abbas Arrak Abbas al-Tamimi (College of Pharmacy / Mustansiriyah University, 2012)
Forty four anti-HCV positive and twenty anti-HCV negative individuals were included in this study for the assessment of interleukin (IL)-6 concentrations and the frequency of C-reactive protein (CRP). Data obtained were statistically analyzed for the significance of differences and correlation between parameters studied.The results showed that CRP frequency was equal in anti-HCV positive and negative individuals, whereas IL-6 found to be elevated in 50% of anti-HCV positive patients. HCV infection found to be positively associated in most cases with increased levels of IL-6. The results suggested that il-6 and CRP levels varied during the course of HCV infection and do not reflect the extent of liver inflammation in HCV patients.